Pattern of Candida Species Isolated from Patient with Vulvovaginal Candidiasis in Pregnancy - Purnamasari, Indah; Ervianti, Evy; Damayanti, Damayanti; Budi Prasetyo; Astari, Linda; Pepy D. Endraswari; Listiawan, M. Yulianto; Cita Rosita Sigit Prakoeswa (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2022)
Background: Vulvovaginal candidiasis (VVC) is one of the most prevalent genital tract diseases in women. The identification of the isolated Candida species is critical for guiding empirical antifungal therapy. Purpose: To determine the Candida species that cause vulvovaginal candidiasis in pregnancy at the Obstetrics and Gynecology Outpatient Clinic, Dr. Soetomo General Academic Hospital, thus providing scientific and therapeutic benefits. Methods:  Pregnant woman receiving antenatal care (ANC) at Dr. Soetomo General Academic Hospital Obstetric and Gynecology Outpatient Clinic. Subjects were enrolled in a cross-sectional study during 3 months between March and May 2021. Vaginal swab samples were taken from subjects after informed consent. A specific color change in CHROMagar cultures and VITEK 2 compact were used to identify Candida species. Result: During the study period, 15 pregnant patients were diagnosed with VVC. The majority of the women in the study were pregnant women of sexually active age who complained of a whitish body and genital irritation. There were 18 candida isolates from CHROMagar cultures, with C. non albicans (61.1%) predominating over C. albicans (38.3%). With details, non albicans were C. glabrata (54.4%), C. dubliniensis (36.3%), and C. parapsilosis (18.1%). Conclusion: This study revealed a high prevalence of Candida non-albicans species causing VVC. Culture investigation and identification of Candida are critical to avoid diminished susceptibility to antifungal treatments and recurrence.